The role of resilience and motivation for improving Indonesian suburban teacher performance - Mudhofar, Ahmad; Rahmat, Pupu Syaeful (Institute of Computer Science (IOCS), 2023)
Teachers are an important component in the teaching and learning process to produce quality students. So, to create quality students, one way is to increase teacher resilience. Teacher resilience in facing difficult conditions needs to be a concern of school leaders in efforts to improve the quality of education, with the assumption that resilience will improve teacher performance and determine the achievement of educational goals. Apart from teacher resilience, motivation from the school also plays an important role. If school motivation is low, it will have a negative impact on teacher performance. With this phenomenon, there is a possibility of a decline in the performance of suburban teachers. The success of schools in improving teacher performance can be influenced by providing training to improve the quality of teacher resources at work, one of which is training for teacher resilience in overcoming teaching obstacles and facing difficult conditions. This quantitative research is the result of community service development carried out by Program Gerakan Desa Mengajar, with the aim of testing the effect of teacher resilience training and providing motivation on improving the performance of 100 (one hundred) honorary teachers in Cirebon Regency. The hypothesis was tested using Partial Least Square (PLS) data analysis. The results show that self-resilience training improves teacher performance, while motivation does not play a role in improving the performance of Sub Urban teachers in Cirebon Regency.